The Recovery Myth The Plans and Situated Realities of Post-Disaster Response - Easthope, Lucy (Springer International Publishing, 2018)
This book provides an innovative re-examination of the 'recovery' phase of a disaster by one of the UK's most experienced disaster management specialists. Drawing on two decades' of work, the book develops an ethnography of the residents and responders in one flooded village and applies this to other cases of UK flooding, as well as to post-disaster recovery in New Zealand. The book shows how localised emergency responders find ways to collaborate with residents, and how an informal network uses nationally generated instruments differently to co-produce regeneration within a community. The book considers the plethora of government instruments which have been produced to affect recovery, including checklists, templates and guidance documents, and discusses approaches to community resilience and recovery risk management. The book appeals to students and scholars of Government and Public Policy, Disaster and Emergency Management, Community Resilience, Law, Sociology and Geography. Lucy Easthope is Deputy Director of Research, Lincoln Law School, University of Lincoln, UK, Senior Fellow of the Emergency Planning College and Research Affiliate at the Joint Centre for Disaster Research.